2018
DOI: 10.1016/j.jcrysgro.2018.02.014
|View full text |Cite
|
Sign up to set email alerts
|

α-Ga2O3 grown by low temperature atomic layer deposition on sapphire

Abstract: -Ga2O3 is a metastable phase of Ga2O3 of interest for wide bandgap engineering since it is isostructural with -In2O3 and -Al2O3. -Ga2O3 is generally synthesised under high pressure (several GPa) or relatively high temperature (~500 o C). In this study, we report the growth of -Ga2O3 by low temperature atomic layer deposition (ALD) on sapphire substrate. The film was grown at a rate of 0.48 Å/cycle, and predominantly consists of -Ga2O3 in the form of (0001)-oriented columns originating from the interface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
60
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 32 publications
14
60
2
Order By: Relevance
“…From our XRD results (Figure 1(B)), the film is dominantly α-Ga2O3. The structure of this film, that is, α phase columns, agrees well with our earlier report 33 . It can be seen that in comparison with Figure 3(A), there is a slight increase in surface roughness related to the grain boundaries where α-Ga2O3 columns touch.…”
Section: Figure 3: Cross-sectional Adf-stem Images Of the Ga2o3 Filmssupporting
confidence: 92%
See 2 more Smart Citations
“…From our XRD results (Figure 1(B)), the film is dominantly α-Ga2O3. The structure of this film, that is, α phase columns, agrees well with our earlier report 33 . It can be seen that in comparison with Figure 3(A), there is a slight increase in surface roughness related to the grain boundaries where α-Ga2O3 columns touch.…”
Section: Figure 3: Cross-sectional Adf-stem Images Of the Ga2o3 Filmssupporting
confidence: 92%
“…The XRD peaks seen in Figure 1 In our previous study of 130 nm thick Ga2O3 films, we observed by SED that the ca. 70 nm of Ga2O3 material adjacent to the substrate was dominantly α phase columns with a diameter of 2-23 nm 33 . Since the films shown here are approximately 30 nm thick, we expect that the grain-like structure observed here by AFM corresponds to the termination of the α phase columns.…”
Section: Analysis Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…To better understand the origin of this variation, TEM imaging of the as-grown sample, of the sample annealed in oxygen, and of the forming gas annealed sample was conducted. As illustrated in Figure 5, all three samples are nearly identical; they exhibit a columnar structure of α-Ga2O3 separated by amorphous Ga2O3 [21] and the columns have visually similar width and height. It appears that all the annealed samples A c c e p t e d M a n u s c r i p t exhibit a columnar structure (from TEM observations); a comparable α phase volume fraction or crystallite size (from XRD 2θ-ω scans); and similar strain state (from XRD RSMs).…”
Section: Samplementioning
confidence: 93%
“…Using atomic layer deposition (ALD), most studies have reported the deposition of amorphous Ga2O3 films [14][15][16][17][18][19][20]. However, it has been recently demonstrated that α-Ga2O3 could also be synthesized using plasma-enhanced ALD at temperatures as low as 250 o C [21]. To date, the body of work on this material has focused on growth aspects, and only a limited number of studies have reported the application of the grown materials in devices.…”
Section: Introductionmentioning
confidence: 99%